A Threat of Polarization: Race, Religion, and Reform - U Tun Aung, Maulana Akbar Shah (2023)
Lately, there seems to be a growing divide among people with varying beliefs, opinions, faiths, and ethnic backgrounds. This can cause a rift between individuals and groups, leading to polarization. Polarization refers to dividing people or groups into opposing factions or beliefs. A lack of communication and understanding between these groups often characterizes it. It's disheartening to see the polarization that still exists among different races and religions. It's a problem that has persisted for far too long and has caused so much pain and suffering. We need to work towards finding common ground and embracing our differences instead of letting them divide us. Only then we can truly move forward as a united and peaceful society. In the context of race, polarization can lead to increased tensions between different racial groups and a lack of empathy and understanding between them. This can result in discrimination, prejudice, and even violence. Polarization can also make it difficult to address systemic issues that disproportionately affect certain racial groups, as there may be a lack of consensus on the issues or how to address them. Ultimately, polarization in race can have negative impacts on individuals, communities, and society as a whole. Polarization can also manifest in inter-religious and intra-religious contexts. It can lead to increased tensions between different religious groups, as well as within the same religious community. This can result in a lack of responsiveness and tolerance between individuals of different faiths or denominations and can contribute to discrimination, prejudice, and even violence. Polarization within a religion can also lead to ideological divisions and schisms, which can further exacerbate inter-religious tensions. Ultimately, polarization in religion can have negative impacts on individuals, communities, and society as a whole. It is important to work towards promoting understanding and empathy between different religious groups and within the same religious community to prevent the negative effects of polarization. To address the issues of polarization in the race and religion sectors, we need to implement a reform process that can effectively resolve the underlying problems. Reform can play a crucial role in addressing the problems of racial and religious polarization. Promoting inclusivity and diversity, and challenging discriminatory practices and beliefs, can help bridge the divides between different groups. Reform can also encourage dialogue and understanding between individuals of different faiths and races and can create opportunities for cooperation and collaboration. Ultimately, reform can help build a more just, equitable, and harmonious society. The qualitative research methodology will be applied in this research and it will be published in an indexed journal this year, 2023.